Feasibility and performance analysis of bifacial module under extremely hot and dry climate. (1st March 2023) - Verma, Deepak; Shah, Jainam; Patel, Nisarg; Patel, Rushil; Patel, Dhruvil
Abstract: Solar panels with a bi-facial design provide energy from both sides; thus, it would be interesting to examine the viability of such modules in an extremely hot and dry city like Ahmedabad, Gujarat, India. This study assesses the temperature, efficiency, and bifacial gain of PV bifacial modules as a function of solar irradiation, ambient temperature, wind speed, and additional parameters. The global horizontal irradiance has been used in this study to calculate Direct Normal Irradiance (DNI), Diffuse Horizontal Irradiance (DHI) and Front and Rear Irradiance. The results show that an optimal tilt angle of 43.5° provides the best efficiency of 24% at ambient temperature. For a constant value of tilt angle, the bi-facial gain of the module increases linearly with albedo factor. It has also been discovered that continuing to raise the elevation beyond 1 meter will eventually diminish the bifacial gain because the reflected and diffuse irradiance will become less intense on the rear side of the bifacial module.